Molecular insights into chronotype and time-of-day effects on decision-making - Ingram, Krista; Ay, Ahmet; Kwon, Soo Bin; Woods, Kerri; Escobar, Sue; Gordon, Molly; Smith, Isaac; Bearden, Neil; Filipowicz, Allan; Jain, Kriti (Nature Publishing Group, 2016)
Recent reports highlight that human decision-making is influenced by the time of day and whether one is a morning or evening person (i.e.,chronotype). Here,we test whether these behavioral effects are associated with endogenous biological rhythms. We asked participants to complete two well-established decision-making tasks in the morning or evening: the matrix task (an ethical decision task) and the balloon analog risk task (BART; a risk-taking task),and we measured their chronotype in two ways. First,participants completed a self-report measure,the Horne-Östberg Morningness-Eveningness Questionnaire (MEQ). Second,we measured the expression of two circadian clock-regulated genes - Per3 and Nr1d2 - from peripheral clock cells in participants' hair follicle samples. Using a cosinor model,we estimated the phase of the peripheral clock and assigned RNA chronotypes to participants with advanced (larks) or delayed (owls) phases. The behavioral data were analyzed independently for self-reported (MEQ) and RNA-based chronotypes. We find that significant chronotype and/or time-of-day effects between larks and owls in decision-making tasks occur only in RNA-based chronotypes. Our results provide evidence that time-of-day effects on decision-making can be explained by phase differences in oscillating clock genes and suggest that variation in the molecular clockwork may influence inter-individual differences in decision-making behavior.
Keywords: cell receptor; circadian rhythm signaling protein; NR1D2 protein; human; PER3 protein; human; repressor protein; chemistry; circadian rhythm; decision making; female; genetics; hair follicle; human; male; self report; sleep; theoretical model; time factor; young adult; Circadian Rhythm; Decision Making; Female; Hair Follicle; Humans; Male; Models; Theoretical; Period Circadian Proteins; Receptors; Cytoplasmic and Nuclear; Repressor Proteins; Self Report; Sleep; Time Factors; Young Adult; 32 Ciencias Médicas; ODS 3 - Salud y bienestar